TEORI HUKUM PEMBANGUNAN ANTARA DAS SEIN DAN DAS SOLLEN - Akbar, Kemas Ilham; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The current Legal Theory of Development is a product designed by Indonesians, with adjustments that reflect local cultural contexts and values. This theory was formed, grew, and developed from Indonesia's unique conditions, so its application requires special attention to the diversity and social circumstances of local communities. The challenge faced is how to integrate this theory into the national legal system and the extent of its influence on legal reform in Indonesia, both in reality (das sein) and ideal (das sollen). This research uses a normative juridical method with a descriptive approach, in which secondary data is analyzed qualitatively and concluded with a deductive logic approach. The results show that the application of Legal Development Theory in the National Legal System reflects the aspirations of the community in assessing the implementation of the current law. The impact of this theory on the modernization of national law confirms the ideal concept (sollen) which is recognized and reflected in the social reality (sein) of society.Keywords: Legal Development, Das Sein, Das Sollen